(untitled) (Archaeologia Adriatica, 2013)
The article briefly presents role of medieval archaeology in the study of archaeology in Zadar. Present and past courses of the study are mentioned. Most important research activities of the professors from the Chair in Medieval and Postmedieval Archaeology are described in brief.